Determinants for persistence of Pseudomonas aeruginosa in hospitals: interplay between resistance, virulence and biofilm formation - Kaiser, Stefan J.; Mutters, Nico T.; Frank, Uwe; Günther, Frank (European journal of clinical microbiology & infectious diseases, 2017)
Pseudomonas aeruginosa (Pa) is one of the major bacterial pathogens causing nosocomial infections. During the past few decades, multidrug-resistant (MDR) and extensively drug-resistant (XDR) lineages of Pa have emerged in hospital settings with increasing numbers. However, it remains unclear which determinants of Pa facilitated this spread. A total of 211 clinical XDR and 38 susceptible clinical Pa isolates (nonXDR), as well as 47 environmental isolates (EI), were collected at the Heidelberg University Hospital. We used RAPD PCR to identify genetic clusters. Carriage of carbapenamases (CPM) and virulence genes were analyzed by PCR, biofilm formation capacity was assessed, in vitro fitness was evaluated using competitive growth assays, and interaction with the host’s immune system was analyzed using serum killing and neutrophil killing assays. XDR isolates showed significantly elevated biofilm formation (p < 0.05) and higher competitive fitness compared to nonXDR and EI isolates. Thirty percent (62/205) of the XDR isolates carried a CPM. Similarities in distribution of virulence factors, as well as biofilm formation properties, between CPM+ Pa isolates and EI and between CPM- and nonXDR isolates were detected. Molecular typing revealed two distinct genetic clusters within the XDR population, which were characterized by even higher biofilm formation. In contrast, XDR isolates were more susceptible to the immune response than nonXDR isolates. Our study provides evidence that the ability to form biofilms is an outstanding determinant for persistence and endemic spread of Pa in the hospital setting.